Regulation by Blockchain: the Emerging Battle for Supremacy between the Code of Law and Code as Law. - Yeung, Karen (Modern Law Review, 2019)
This paper critically examines the intersection and interactions between conventional law produced and enforced by national legal systems (ie the 'code of law') and the internal rules of blockchain systems, which take the form of executable software code and cryptographic algorithms operating across a distributed computing network ('code as law').  In so doing, it seeks to identify whether, and to what extent, 'regulation by blockchain' will successfully avoid governance by conventional law.   It identifies three different ways in which the code of law is likely to interact with code as law, based primarily on the intended motives and purposes of those engaged in activities in developing, maintaining or undertaking transactions upon the network.  It argues that these different classes of case are likely to generate different kinds of dynamic interaction between the blockchain code and conventional legal systems, and critically examines the normative foundations of these emerging and anticipated interactions.